The Growing Obesity Epidemic: Integrating Lifestyle, Pharmacological, and Surgical Interventions for Effective Management - Siwiec, Jan; Śpiołek, Olga; Wąsowicz, Agnieszka; Sztyler-Krąkowska, Marcelina; Teofilak, Mateusz; Smyl, Natalia; Słowikowska, Aleksandra; Szatkowska, Julia; Kędziora, Franciszek; Fabian, Dariusz (Journal of Education, Health and Sport, 2025)
Introduction: Obesity is a multifactorial disease with a growing global prevalence, significantly increasing the risk of numerous health conditions, including type 2 diabetes and cardiovascular diseases. Its management requires a multifaceted approach that includes lifestyle modifications, pharmacologic interventions and, in severe cases, surgical treatments. Materials and methods: A literature review was conducted using PubMed and Google Scholar, using keywords: “obesity epidemiology”, “obesity consequences”, “obesity treatment”, “obesity pharmacology” Conclusions: The prevalence of obesity is rising worldwide, with genetic, environmental, and lifestyle factors contributing to its development. Effective obesity management involves personalized interventions, including dietary and behavioural changes, alongside pharmacological options like GLP-1 receptor agonists and naltrexone-bupropion. Surgical interventions are considered for severe cases. Emerging treatments, such as tirzepatide, targeting both GLP-1 and GIP receptors, show promising results. A comprehensive, individualized approach remains crucial for improving patient outcomes and addressing the global obesity epidemic.